Image-guided fine-needle aspiration cytology or core biopsy – A key to definitive diagnosis of tuberculous mastitis - Shirish Sahebrao Chandanwale; Rajeshwari Ravishankar; Anshita Atul Garg; Mayur Ravindrarao Ambekar (International Journal of Mycobacteriology, 2022)
Despite advances in the treatment, tuberculosis (TB) is still a global health problem. The diagnosis of extrapulmonary TB in their primary form is very challenging. Breast TB is very uncommon and accounts for < 0.1% of all breast lesions. Due to rarity of the disease and difficulty in diagnosis, we report a case of a 40-year-old female who had a hard lump in the right breast. Full-field digital mammography suggested the lesion as American College of Radiology Breast Imaging Reporting and Data System-5 (ACR BIRADS-5) (highly suggestive of carcinoma). Histopathological examination of multiple cores of the breast tissue showed lymphocytic inflammatory infiltrates confined to breast lobules. Fungal stains and Ziehl–Neelsen (ZN) stain were negative. A diagnosis of chronic mastitis with the possibility of autoimmune lobular mastitis was suggested. Subsequent image-guided fine needle aspiration smears showed epithelioid granulomas mixed with lymphocytes. Areas of amorphous-to-granular eosinophilic material (caseous necrosis) were seen at places. ZN stain showed acid-fast bacilli. A diagnosis of tuberculous mastitis was given.